Implications of Quercetin in Mitigating Myocardial Ischemia-Reperfusion Injury: A Review Study - Shirin Azizidoost; Maryam Adelipour; Habib Haybar; Zahra Shabaninejad; Mojtaba Rashidi (Advanced Biomedical Research)
Myocardial ischemia-reperfusion injury (IRI) is introduced as a typical cardiovascular disorder with enhancing worldwide occurrence. It is generally persuaded via normal blood flow restoration to the ischemic myocardium after a recanalization period and instantly results in myocardial damage. Current investigations displays that flavonoids have the capability to function as cardioprotective agents versus IRI, which are faced in the myocardium. In this comprehensive review, we aim to delineate the therapeutic effects of quercetin in the context of myocardial IRI, shedding light on its potential as a cardioprotective agent. An up-to-date review of the literature on the cardioprotective impact of quercetin in myocardial IRI was conducted through Embase, all databases correlated to Science Direct, and Pubmed using the terms “myocardial ischemia”, “reperfusion injury” and “quercetin”. Quercetin exhibits protective effects against IRI through its anti-inflammatory, antioxidant, antiapoptotic, and calcium overload-reducing activities. The present review can emerge as a reference for planning a daily diet to prohibit or alleviate injuries following myocardial IRI and emerging flavonoids as a new window for clinical application.